Integration Food, Feed, Fuel and Fertilizer Systems in Kolaka Regency - Zakariah, Muhammad Askari (Fakultas Dakwah dan Ilmu Komunikasi, 2019)
Integration provides relationships between sub-systems with other sub-systems in an area that can be called agro industry. With the development of the integration method model in the main production process, side and waste make and encourage agro industry can be low external input sustainable agriculture. So that with the approach of developing the integration method the system model gets a model to synchronize the sub-systems of agriculture, plantations and livestock into an integration of food, feed, fuel, fertilizer in increasing the productivity of Islamic Farmers in Kolaka and Kolaka Timur. A number of actors involved in the integration system of food, feed, fuel and fertilizer: 1). Cattle Breeders, require availability of feed raw materials, controlled volume of waste. 2). Rice farmers, need superior seeds, good irrigation systems, and fertilizers. 3). Cocoa farmers, need superior seeds, good irrigation systems, and fertilizers. 4). Clove farmers, need superior seeds, good irrigation systems, and fertilizers. 5). Local people, need animal and biological food, need a beautiful environment, no pollution / pollution to the soil, water and air.